PENERAPAN METODE BERMAIN, CERITA DAN MENYANYI (BCM) DALAM MENINGKATKAN MOTIVASI BELAJAR AL-QUR’AN DI TAMAN PENDIDIKAN AL-QUR’AN BAITUL GHAFFAR PERUMAHAN BUMI ASRI SENGKALING MALANG - Fathma Raghida; Muhammad Hanief; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
In general, the success of an education, including Al-Qur'an education in achieving its objectives is not independent, but is related to several factors. Among other things, learning method factors. In learning to read the Koran there are several methods used to develop a child's ability to read the Koran. Among these are the BCM method. This method is psychologically visible in line with the mental development of children who generally like to listen to stories, play and sing. Therefore, the authors are interested in examining the application of the TPQ method in Baitul Ghaffar located in Bumi Asri Sengkaling Malang housing. In this study the approach used by researchers is qualitative research with a type of phenomenology study. The presence of researchers in the field is a key instrument in collecting data. The procedure for collecting data in this study was taken using interview methods, documentation and observation. While the analysis uses descriptive analysis. Checking the validity of the data in this study included: data triangulation, method triangulation and source triangulation. From the results of the study it can be found that the BCM method is very effective to be used for Al-Qur'an learning for child TPQ students. In addition, the motivation of the supporters is also very influential in the implementation of ongoing learning activities. Therefore this method is used as a supporting method in Baitul Ghaffar's TPQ.Keywords: BCM Method, Increasing Motivation for Learning Al-Qur'an, TPQ.